Lafcadio Hearn's America : ethnographic sketches and editorials - Hearn, Lafcadio, 1850-1904 (University Press of Kentucky, 2002)
The American essays of renowned writer Lafcadio Hearn (1850-1904) artistically chronicle the robust urban life of Cincinnati and New Orleans. Hearn is one of the few chroniclers of urban American life in the nineteenth century, and much of this material has not been widely available since the 1950s. Lafcadio Hearn's America collects Hearn's stories of vagabonds, river people, mystics, criminals, and some of the earliest accounts available of black and ethnic urban folklife in America. He was a frequently consulted expert on America during his years in Japan, and these editorials reflect on th.
Keywords: Hearn, Lafcadio, -- 1850-1904 -- Homes and haunts -- Anecdotes.; Hearn, Lafcadio, -- 1850-1904 -- Political and social views.; Hearn, Lafcadio, -- 1850-1904; United States -- Description and travel -- Anecdotes.; United States -- Social life and customs -- 1865-1918 -- Anecdotes.; United States -- Social conditions -- 1865-1918 -- Anecdotes.; Ethnology -- United States -- History -- 19th century -- Anecdotes.; Social classes -- United States -- History -- 19th century -- Anecdotes.; États-Unis -- Mœurs et coutumes -- 1865-1918 -- Anecdotes.; États-Unis -- Conditions sociales -- 1865-1918 -- Anecdotes.; Ethnologie -- États-Unis -- Histoire -- 19e siècle -- Anecdotes.; Classes sociales -- États-Unis -- Histoire -- 19e siècle -- Anecdotes.; LITERARY COLLECTIONS -- Essays.; Ethnology; Homes; Manners and customs; Political and social views; Social classes; Social conditions; Travel; United States; 1800-1918; Anecdotes; History